2012
DOI: 10.1021/ma300085a
|View full text |Cite
|
Sign up to set email alerts
|

Interchain Monomer Contact Probability in Two-Dimensional Polymer Solutions

Abstract: Using molecular dynamics simulation of a standard bead-spring model we investigate the density crossover scaling of strictly two-dimensional (d = 2) self-avoiding polymer chains focusing on properties related to the contact exponent θ2 set by the intrachain subchain size distribution. With R ∼ N ν being the size of chains of length N , the number nint of interchain monomer contacts per monomer is found to scale as nint ∼ 1/N νθ 2 with ν = 3/4 and θ2 = 19/12 for dilute solutions and ν = 1/d and θ2 = 3/4 for N ≫… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Polymer blends. As already argued elsewhere [6,15], the presented numerical results for the interchain interaction energy e int for homopolymer systems implies an enhanced compatibility for polymer blends confined to ultrathin films in qualitative agreement with recent experimental studies [24]. We remind that the critical temperature of unmixing T c should be proportional to the typical interaction energy Ne int between different chains.…”
Section: E Stress Fluctuationssupporting
confidence: 90%
See 3 more Smart Citations
“…Polymer blends. As already argued elsewhere [6,15], the presented numerical results for the interchain interaction energy e int for homopolymer systems implies an enhanced compatibility for polymer blends confined to ultrathin films in qualitative agreement with recent experimental studies [24]. We remind that the critical temperature of unmixing T c should be proportional to the typical interaction energy Ne int between different chains.…”
Section: E Stress Fluctuationssupporting
confidence: 90%
“…As in ref. [15] where we have discussed various conformational properties of semidilute solutions and melts we scan over a broad range of densities ρ. All properties reported for ρ ≤ 0.25 have been sampled using MC [42].…”
Section: Coarse-grained Polymer Model and Computational Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of small-angle neutron scattering have shown that polymer gels have similar characteristics as dense fluids of hard spheres [53]. Recent simulations agree with this granular or blob description of polymers [54]. Similar granular descriptions have also been associated with acoustic dispersion phenomena, wherein the grain size in materials such as polymers has been interpreted as the free path between acoustic scattering sites [55].…”
Section: Mathematical Modelmentioning
confidence: 91%